2015
DOI: 10.15252/embr.201541677
|View full text |Cite
|
Sign up to set email alerts
|

Biometrics' new identity—measuring more physical and biological traits

Abstract: Biometric measurements have the potential to improve both security and convenience in many areas of our daily lives, including in health care and social services. Researchers are exploring new biometric characteristics that could be used to develop full‐proof methods to assess and validate someone's identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Limitations with UPIs and matching algorithms have led to the exploration of other add-on technologies including biometric identification technologies. Such approaches include fingerprints, palm vein scanning, iris scanning, and facial recognition 41 . Biometric identification technologies are advantageous because biometrics data is more difficult to “steal, exchange or forget” 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Limitations with UPIs and matching algorithms have led to the exploration of other add-on technologies including biometric identification technologies. Such approaches include fingerprints, palm vein scanning, iris scanning, and facial recognition 41 . Biometric identification technologies are advantageous because biometrics data is more difficult to “steal, exchange or forget” 25 .…”
Section: Resultsmentioning
confidence: 99%
“…photos) or even remotely via technology (e.g. social media) without necessarily gaining the express permission of an individual (Arigbabu et al, 2014; Rinaldi, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The NHS lists patient misidentification as serious patient safety incidents that should not occur. 61 EEG is an important tool for the assessment of brain development in newborns. [62][63][64][65] It has been found that coherent EEG activity during sleep may provide unique insight into maturation processes of brain functional connectivity.…”
Section: Possible Application Areas and Future Workmentioning
confidence: 99%